PENGARUH KECEMASAN BELAJAR DAN KECERDASAN ANALITIK TERHADAP KEMAMPUAN BELAJAR STATISTIKA - Permana, Adi (Universitas Islam Sumatera Utara, 2019)
Abstract. The purpose of this study was to determine the effect of anxiety and intelligence analytic study on the ability to learn statistics. The research was conducted on university students Indraprasta Indonesian education courses. The sample consisted of 60 students. Samples were taken by random sampling technique. The method used in this research is the survey method with correlation and regression analysis. The results of this study prove the influence of anxiety and intelligence analytic study on the ability to learn statistics. The magnitude of the correlation between variables correlation anxiety and intelligence analytic study together with the ability to learn statistics is 0.743, which means the correlation is strong. anxiety and intelligence analytic study jointly contribute statistical learning ability by 55.2%, while the rest influenced by other factors. While the regression equation formed between the anxiety of learning and intelligence analytic and statistical learning ability is Y = 24.51 + 0,247X1 + 0,145X2Keywords: Anxiety Learning, Intelligence Analytical, the ability of Statistics, Influence.